ECO-EFFICIENCY TERHADAP NILAI PERUSAHAAN DENGAN DIMEDIASI PROFITABILITAS DAN DIMODERASI FIRM SIZE - Atiningsih, Suci; Setiyono, Taufiq Andre (Universitas Muhammadiyah Palembang, 2023)
The aim of this research is to empirically examine the effect of eco-efficiency on firm value mediated by profitability and moderated by firm size. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique used purposive sampling and obtained a company with a total sample of 249 samples. Hypothesis testing using multiple regression analysis. The results of this study are eco-efficiency and profitability have an effect on firm value, profitability cannot mediate the effect of eco-efficiency on firm value, and firm size can moderate the effect of eco-efficiency on firm value. The contribution of this research is to provide input for companies and also for external parties in making decisions related to eco-efficiency management and its impact on company value. The limitations of this study are that the research object used is limited to manufacturing companies listed on the Indonesia Stock Exchange, so that the sample used is less broad and cannot accurately describe the extent of company value in Indonesia.